2019
DOI: 10.1007/s12630-019-01301-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidural electrical stimulation test versus local anesthetic test dose for thoracic epidural catheter placement: a prospective observational study

Abstract: Purpose This study examined the concordance between epidural electrical stimulation test (EEST) and local anesthetic (LA) test dose to indicate correct thoracic epidural catheter position. The relationship between the test results and epidural postoperative analgesia was also assessed. Methods This prospective observational cohort study was done in patients receiving thoracic epidural analgesia for abdominal surgery. After insertion, the epidural catheter was tested using a nerve stimulator to elicit a motor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
(35 reference statements)
0
9
0
4
Order By: Relevance
“…It is essential to create a continuous column of conducting fluid within the stainless-steel wire-reinforced epidural catheter by priming it with saline after insertion and to ensure that there is no air within the system. 3 We have found that application of gentle continuous pressure on the saline column during stimulation facilitates a reliable and repeatable evoked motor response. It is notable that most studies evaluating the test do not use a stimulating catheter.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…It is essential to create a continuous column of conducting fluid within the stainless-steel wire-reinforced epidural catheter by priming it with saline after insertion and to ensure that there is no air within the system. 3 We have found that application of gentle continuous pressure on the saline column during stimulation facilitates a reliable and repeatable evoked motor response. It is notable that most studies evaluating the test do not use a stimulating catheter.…”
mentioning
confidence: 93%
“…Though the adoption of the EEST in adults appears to be quite slow, the clinical need to decrease thoracic epidural block failure is well documented. We hope that the study by Balki et al 3 will remind clinicians that the EEST is a superior option when objective confirmation of epidural catheter positioning is sought. We are confident that routine adoption of the EEST will help to maximize the benefits derived from epidural analgesia.…”
mentioning
confidence: 97%
See 3 more Smart Citations